The Role of Positive Emotion in Increasing Impulse Buying - Listriyani, Listriyani; wahyono, wahyono (Management Analysis Journal, 2019)
The purpose of this study is to determine the direct and indirect influence of visual merchanding, sales promotion and shopping lifestyle toward impulse buying through positive emotion as an intervening variable. Positive emotion influence customers to make an impulse buying. The population in this research is customers of Duta Mode Purwokerto. The total sample in this research is 115 respondents with incidental sampling technique through a likert scale. Methods of collecting data using questionnaires and documentation. Data analysis using classic assumption test and hypothesis test (t test and path analysis) with SPSS Statistics version 21 programs. Based on the hypothesis test, the results show that visual merchandising has a positive and significant effect on impulse buying, sales promotion has a positive and significant effect on impulse buying, shopping lifestyle does not has a positive and significant effect on impulse buying, and positive emotion has a positive and significant effect on impulse buying. Mediation test shows that positive emotion mediates the effect of visual merchandising, sales promotion, and shopping lifestyle on impulse buying.